1993
DOI: 10.1007/bf00144587
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ethylene with indole-3-acetic acid in regulation of rooting in pea cuttings

Abstract: Cuttings of pea (Pisum sativum L . cv Marma) were treated with 1-aminocyclopropane-l-carboxylic acid (ACC) . This treatment caused increased ethylene production and reduction of root formation . The effect of 0 .1 mM ACC on the level of endogenous indole-3-acetic acid (IAA) in the rooting zone and in the shoot apex was analyzed by gas chromatography-single ion monitoring mass spectrometry or by high pressure liquid chromatography with fluorimetric detection (HPLC) . Concentrations of indole-3-acetylaspartic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Ethylene appeared to inhibit adventitious root formation from pea cuttings (Nordstrom and Eliasson 1993), tomato leaf discs (Coleman et al 1980) and Prunus avium shoot cultures (Biondi et al 1990), whereas it was found to stimulate root formation from Norway spruce hypocotyl segments (Bollmark and Eliasson 1990) and hazelnut cotyledons (Gonzalez et al 1991). The promotive effect of ethylene on rooting is mediated by auxin in sunflower hypocotyls (Liu and Reid 1992) and mung bean cuttings (Riov and Yang 1989).…”
Section: Introductionmentioning
confidence: 92%
“…Ethylene appeared to inhibit adventitious root formation from pea cuttings (Nordstrom and Eliasson 1993), tomato leaf discs (Coleman et al 1980) and Prunus avium shoot cultures (Biondi et al 1990), whereas it was found to stimulate root formation from Norway spruce hypocotyl segments (Bollmark and Eliasson 1990) and hazelnut cotyledons (Gonzalez et al 1991). The promotive effect of ethylene on rooting is mediated by auxin in sunflower hypocotyls (Liu and Reid 1992) and mung bean cuttings (Riov and Yang 1989).…”
Section: Introductionmentioning
confidence: 92%